Association between ethylene oxide exposure and cognitive function in older adults from NHANES data - Meng Sun; Meng Cai; Sisi Sun; Huan Liu; Guo Chen (Scientific Reports)
Abstract Ethylene Oxide (EO), a volatile organic compound, has garnered considerable attention for its potential impact on human health. Yet, the ramifications of EO exposure on the cognitive functionality of the elderly remain unclear. The aim of this study is to determine whether EO exposure in the elderly correlates with cognitive function. In this cross-sectional study, an analysis was conducted on 471 participants from the 2013 to 2014 United States National Health and Nutrition Examination Survey (NHANES). T1, T2, and T3 was used to represent the low, moderate, and high tertiles of log10-transformed HbEO levels, respectively. Weighted linear regression analysis, weighted logistic regression analysis, and restricted cubic spline models were employed to assess the association between HbEO and standardized z-scores of four cognitive tests. Firstly, analysis of variable characteristics across the different log10-transformed HbEO groups revealed that HbEO was higher in males, non-Hispanic whites, and smokers and that Z scores for Delayed Recall Test (DRT), Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST) decreased as HbEO increased (p < 0.05). After adjusting for confounding factors, the log10-transformed HbEO levels were found to be negatively correlated with DRT-Z scores (T3 vs. T1 in Model 3: β (95% CI) = − 0.35 (− 0.54, − 0.15), p = 0.002, p for trend = 0.002). In addition, Stratified analyses showed that the four cognitive scores were negatively correlated with HbEO levels in those under 80 years of age. And men had worse AFT scores compared to women. Overall, the four Z-scores roughly trended downward as log10-transformed HbEO rose. Based on the findings of this research, EO exposure may be associated with adverse performance in the DRT among elderly individuals in the United States.